Interventional bronchoscopy : a clinical guide - Jain, Prasoon; Mehta, Atul (Respiratory Medicine, 2013)
The field of interventional bronchoscopy is rapidly expanding and has emerged as a new and exciting subspecialty in pulmonary medicine. To date, the impact of interventional bronchoscopy procedures has been felt in diagnosis, staging, and management of lung cancer, the most lethal cancer worldwide. Interventional Bronchoscopy: A Clinical Guide provides a state-of-the art description of interventional bronchoscopy procedures, addressing the scientific basis, indications, techniques, results, complications, and cost issues. Chapters address the current status, the advantages of new techniques and, most importantly, when to choose new techniques over the existing techniques. Each chapter will discuss the future of these procedures. Interventional Bronchoscopy: A Clinical Guide is an essential resource for a successful interventional pulmonology service and will be useful for the bronchoscopist, anesthesiologist, radiologist, thoracic surgeon and oncologist as well as practicing pulmonologists who do not perform these procedures but have to make decisions regarding appropriate referral of their patients to advanced airway centers.